Reactogenicity, safety, and immunogenicity of chimeric haemagglutinin influenza split-virion vaccines, adjuvanted with AS01 or AS03 or non-adjuvanted: a phase 1–2 randomised controlled trial. Issue 7 (July 2022) - Folschweiller, Nicolas; Vanden Abeele, Carline; Chu, Laurence; Van Damme, Pierre; García-Sastre, Adolfo; Krammer, Florian; Nachbagauer, Raffael; Palese, Peter; Solórzano, Alicia; Bi, Dan; David, Marie-Pierre; Friel, Damien; et al.
Summary: Background: One strategy to develop a universal influenza virus vaccine is to redirect the immune system to the highly conserved haemagglutinin stalk domain by sequentially administering vaccines expressing chimeric (c) haemagglutinins with a conserved stalk domain and divergent head domain, to which humans are naive. We aimed to assess the reactogenicity, safety, and immunogenicity of adjuvanted and unadjuvanted investigational supra-seasonal universal influenza virus vaccines (SUIVs) in healthy young adults. Methods: In this observer-masked, randomised, controlled, phase 1–2 trial, we recruited adults aged 18–39 years with no clinically significant conditions from six centres in Belgium and the USA. Participants were randomly assigned to ten equally sized groups via an online system with the MATerial Excellence programme. Vaccines contained heterosubtypic group 1 H8, H5, or H11 haemagglutinin heads, an H1 haemagglutinin stalk, and an N1 neuraminidase (cH8/1N1, cH5/1N1, and cH11/1N1; haemagglutinin dose 15 μg/0·5 mL), administered on days 1 and 57, with a month 14 booster. SUIVs were evaluated in the sequences: cH8/1N1–placebo–cH5/1N1, cH5/1N1–placebo–cH8/1N1, or cH8/1N1–cH5/1N1–cH11/1N1, adjuvanted with either AS03 or AS01, or not adjuvanted. The last group received inactivated quadrivalent influenza vaccine (IIV4)–placebo–IIV4. Primary outcomes were safety (analysed in the exposed population) and immunogenicity in terms of the anti-H1 stalk humoral response at 28 days after vaccination (analysed in the per-protocol population, defined as participants who received the study vaccines according to the protocol). This trial is registered with ClinicalTrials.gov, NCT03275389 . Findings: Between Sept 25, 2017, and March 26, 2020, 507 eligible participants were enrolled. 468 (92%) participants received at least one dose of study vaccine (exposed population), of whom 244 (52%) were included in the per-protocol population at final analysis at month 26. The safety profiles of all chimeric vaccines were clinically acceptable, with no safety concerns identified. Injection-site pain was the most common adverse event, occurring in 84–96% of participants receiving an adjuvanted SUIV or non-adjuvanted IIV4 and in 40–50% of participants receiving a non-adjuvanted SUIV. Spontaneously reported adverse events up to 28 days after vaccination occurred in 36–60% of participants, with no trends observed for any group. 17 participants had a serious adverse event, none of which were considered to be causally related to the vaccine. Anti-H1 stalk antibody titres were highest in AS03-adjuvanted groups, followed by AS01-adjuvanted and non-adjuvanted groups, and were higher after cH8/1N1 than after cH5/1N1 and after a two-dose primary schedule than after a one-dose schedule. Geometric mean concentrations by ELISA ranged from 21 938·1 ELISA units/mL (95% CI 18 037·8–26 681·8) in the IIV4–placebo–IIV4 group to 116 596·8 ELISA units/mL (93 869·6–144 826·6) in the AS03-adjuvanted cH8/1N1–cH5/1N1–cH11/1N1 group 28 days after the first dose and from 15 105·9 ELISA units/mL (12 007·7–19 003·6) in the non-adjuvanted cH5/1N1–placebo–cH8/1N1 group to 74 639·7 ELISA units/mL (59 986·3–92 872·6) in the AS03-adjuvanted cH8/1N1–cH5/1N1–cH11/1N1 group 28 days after the second dose. Interpretation: The stalk domain seems to be a rational target for development of a universal influenza virus vaccine via administration of chimeric haemagglutinins with head domains to which humans are naive. Funding: GlaxoSmithKline Biologicals.